90:oral HTA and priority setting for universal health coverage in Ethiopia: progress, setbacks, and prospects. (28th April 2022) - Erku, Daniel; Wubishet, Befikadu; Ali, Eskindir Eshetu; Gebretekle, Gebremedhin B; Teni, Fitsum Sebsibe
Abstract : Although many countries across the globe have reaffirmed their commitments to achieve universal health coverage (UHC) by 2030, countries with very limited healthcare budgets struggle to provide UHC. The already stretched healthcare budget is further compromised by the current global economic crisis caused by COVID-19 and substantial reduction in external funding. Due to this, the use of a systematic approach to allocate scarce healthcare resource – such as via Health technology assessment (HTA) – has become more important than ever before. In this work, we categorised the challenges and opportunities for HTA institutionalisation in Ethiopia using Kingdon's multiple streams framework into Problem, Policy and Politics. The problem stream explains how conditions become problems and come to the attention of policy makers. In case of HTA, these include, among others, : i) need for adequate, innovative, and sustainable healthcare financing to achieve UHC and reduce mounting OOP expenditure, ii) need for smart spending due to COVID-19 – induced economic contraction, and uncertainty in donor programming. The policy stream represents the process by which alternative policies are generated and selected. HTA can be put forward as a solution to the 'problem' identified above, along with 'Proof of concept' HTA projects to test the proposed policy. This stream can be influenced by local capacity; availability and quality of data sources; role of academic institutions in priority setting, etc. The politics stream explains how favourable macro-level political conditions could help set the agenda. Visible, and key policy actors such as the Health Minister are more likely to affect the policy agenda in line with the political priority. These three streams need to come together when a policy window, a moment in time when policies are more likely to come on to the government's decision agenda, opens for the issue (i.e. HTA institutionalisation).